Diagnostic and therapeutic process of respiratory disorders during sleep - Karolina Maliszewska; Izabela Oleksak; Iwona Welian-Polus; Karolina Gendek; Wiktoria Wilanowska; Kamila Babkiewicz-Jahn; Justyna Matuszewska (Journal of Education, Health and Sport, 2024)
Introduction and purpose